Penyuluhan Meningkatkan Kesehatan Gigi Dan Pemeriksaan Kesehatan Di Pulau Panjang Kecamatan Galang - Desfa Anisa; Mulyana; Fani Farhansyah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Health is important for every human being, where having a healthy body allows everyone to live more productively compared to people who are sick. This activity was carried out by means of counseling and demonstration using teaching aids to elementary school students in Pulau Panjang, Galang District, as well as health checks for the community. In the counseling session, participants were given an understanding of how important it is to maintain dental health and how to maintain dental hygiene by brushing their teeth properly. After the counseling activity was completed, it was continued with a health check-up activity with the community in Pulang Panjang, Galang District. The health check-up included blood pressure checks and blood sugar, cholesterol and uric acid checks. Blood pressure checks were carried out on adults and the elderly considering that the risk of high blood pressure increases with age. After the blood pressure measurement, it was continued with blood sugar, cholesterol and uric acid checks. From the results of the health check-up, it is hoped that the community can find out what diseases they are experiencing. Overall, this counseling and health check-up activity went well.